Knowledge and Skills of Leprosy Among Healthcare Workers and Its Associated Factors in Primary Healthcare - Tengku N. Zafirah MD, MPH; Rafdzah Ahmad Zaki MBChB, DrPH; S. H. Lim PhD; Rafidah Baharudin MBBS; Z. Nur Aiza MD, MPH, OHD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
This study aimed to assess the knowledge and skills of leprosy among healthcare workers (HCWs) and its associated factors in primary healthcare facilities. A total of 150 HCWs from 50 health clinics in six districts in Pahang were assessed using a self-administered knowledge questionnaire and skills assessment checklist, selected through stratified random sampling. The results showed a mean knowledge score of 11.10 (/25) and a median skills score of 12 (/70). HCWs with higher education levels, over 20 years of working experience, and prior leprosy exposure demonstrated better knowledge of the illness. Additionally, male gender and higher education level are associated with greater leprosy-related skills. The study reveals the inadequate knowledge and skills of professionals about leprosy, emphasizing training in diagnosis, prevention, and control of the disease.